Experiencing politics : a legislator's stories of government and health care - McDonough, John E. (John Edward) (California/Milbank series on health and the public, 2000)
John E. McDonough affords a rare glimpse into the practice of state politics in this insider's account of the fascinating interface between political science and real-life politics. A member of the Massachusetts House of Representatives for thirteen years and a skilled storyteller, McDonough eloquently weaves together stories of politics and policy with engaging theoretical models in a way that illuminates both the theory and the practice.